Balloon Laryngoplasty for Subglottic Stenosis Caused by Orotracheal Intubation at a Tertiary Care Pediatric Hospital - Avelino, Melissa Gomes Ameloti; Fernandes, Edson Junior de Melo (International Archives of Otorhinolaryngology, 2014)
Introduction In recent years, there has been a reduction in mortality rates in neonatal intensive care units (NICUs) due to the impact of modern technological advances in the perinatal field. As a consequence, prolonged orotracheal intubation is used more frequently, and there has been an increase in acquired subglottic stenosis (SGS) in children. Subglottic stenosis is a narrowing of the endolarynx and one of the most common causes of stridor and respiratory distress in children. The laryngoplasty balloon has proven effective in dealing with stenosis both as primary and secondary treatments, after open surgery, with the added advantage of being less invasive and not requiring external access.Materials and Methods This study involved children from pediatric intensive care units or NICUs suffering from respiratory distress and who presented an endoscopic diagnosis of Myer and Cotton grade I to III SGS. These patients underwent balloon laryngoplasty with different numbers of interventions depending on the response in each individual case.Results All the patients responded satisfactorily to the balloon laryngoplasty. None required tracheostomy after treatment and all remained asymptomatic even after 6-month follow-up. One patient required just 1 dilation, 4 required 2, 3 underwent the procedure 3 times, and another had 5 dilations.Conclusion The experience presented here is that of balloon laryngoplasty post–orotracheal intubation SGS with very satisfactory results at a tertiary care pediatric hospital. Although the number of patients is limited, our incidence corroborates other studies that demonstrate the efficacy and safety of balloon dilatation in the treatment of SGS.
Keywords: larynx; intubation; pediatrics; laryngoplasty